Enhancement stimulants: perceived motivational and cognitive advantages - Ilieva, Irena P.; Farah, Martha J. (Frontiers in Neuroscience, 2013)
Psychostimulants like Adderall and Ritalin are widely used for cognitive enhancement by people without ADHD, although the empirical literature has shown little conclusive evidence for effectiveness in this population. This paper explores one potential explanation of this discrepancy: the possibility that the benefit from enhancement stimulants is at least in part motivational, rather than purely cognitive. We review relevant laboratory, survey and interview research and present the results of a new survey of enhancement users with the goal of comparing perceived cognitive and motivational effects. These users perceived stimulant effects on motivationally-related factors, especially “energy” and “motivation,” and reported motivational effects to be at least as pronounced as cognitive effects, including effects on "attention."